Climate crisis seen through gender lens - Media for Environment, Science, Health and Agriculture; CGIAR Impact Platform on Climate Change; CGIAR GENDER Impact Platform (MESHA, 2024)
All was not well by the close of COP29 global climate talks in Baku, Azerbaijan in November 2024. The paltry $300 billion annually, pledged by the global North, fell far short of the $1.3 trillion Africa and the rest of the global South had sought to finance climate solutions. Back home, it had been necessary to face the reality, maximise use of locally available resources and repackage Africa, not as a cry-baby in the face of negative impacts of climate change, but also as one with abundant nature-based and other solutions as well as resources. Journalists preparing to cover COP29 needed adequate insight into the spoken and unspoken issues concerning Africa, and how to repackage their stories to speak for the continent. This need was fulfilled through virtual training sessions that dissected critical climate-related issues through the gender lens. They included technology transfer, just transition to renewable energy in the face of recently discovered fossil fuel deposits in Africa, the contentious climate finance, and energy poverty that affects more than 600,000 persons in the continent alone. To amplify their great work around the issues, the CGIAR GENDER Impact Platform and the Climate Impact Platform collaborated with MESHA to spotlight research contributions from the CGIA R to local, national and international climate solutions in agri-food systems. In this edition of ‘Sayansi’, therefore, and with the help of the two CGIA R platforms, journalists have demonstrated that while looking at the global pedestal for solutions to the climate crisis, a great percentage also lies in climate-smart agriculture and gender inclusion in the grassroots. Africa is indeed the continent with immense climate solutions. MESHA journalists further benefited from the collaboration through capacity building activities on evidence-based gender and climate change reporting. More than 30 journalists from the MESHA networks participated in each of two science media Cafés dubbed “Road to Baku”, focusing on climate change and gender reporting. The two Platforms provided technical speakers at the Cafés. Besides, journalists and experts networked. The journalists can now easily reach CGIA R scientists for more insights and story ideas beyond the COP29.